LA DIFFERENCE CONCEPTUELLE ENTRE LA NEGRITUDE, L'ANTILLIANITE ET LA CREOLITE - Baba Abraham Jatoe-Kaleo (European Scientific Journal, ESJ, 2013)
The man of color, the black man, reduced to slavery for centuries, and then subjected to European colonial domination, struggled to free himself from the yoke under which he bowed. The struggle for the liberation and the restoration of his dignity as a man was expressed by means of movements like the Negritude movement, Antillanité and Créolité. These three related literary movements however lay claim to their individual distinctiveness in objectives and reach of issues dealt with. While we concede such differences, it is our considered opinion that they express the same ideas, although differently, due to different emphasis their geopolitical contexts and the experience of their main protagonists impose on them.